Electing Not to Fight: Elections as a Mechanism of Deradicalisation after the Irish Civil War 1922–1938 - Bill Kissane (International Journal of Conflict and Violence, 2012)
Much research into the relationship between democratisation and conflict argues that holding elections soon after civil war, when nationalist issues still resonate, is likely to see voters elect to fight. This paper explores a case where elections had the opposite effect. Examination of the relationship between election results and political developments, as well as geographical voting patterns, demonstrates that elections were the primary mechanism for the deradicalisation of Irish politics after the civil war of 1922–23. Elections served as a mechanism for arbitration, selection, and coordination between more and less radical elites and their bases of support. Once the new state had shown its strength it had to accommodate gradual change, while electoral losers had to show they could reconcile change with stability. Elections helped establish credibility in both respects without altering the state-society relationship, suggesting that deradicalisation was dependent on state performance, and thus on some shared conception of the state. This combination of credibility, electoral legitimacy, and state performance, enabled a revolutionary elite, schooled in both constitutional and revolutionary politics, to deradicalise Irish nationalism after independence.